Estado democrático de direito e o inquérito 4.781/STF: reflexões sobre a defesa institucional no mundo das “fake News” - Klaic, Alex (Universidade do Vale do Rio dos Sinos, 2023)
The present work seeks to understand the situation that allowed an investigation initiated ex officio by the President of the Federal Supreme Court, with the indication of the rapporteur, outside the ordinary distribution, which is processed in secrecy and from which orders of censorship, investigation and even arrest, may exist in the Brazilian Democratic State of Law, under the auspices of the 1988 Federal Constitution. Thus, we sought to examine the phenomenon of current times from the extremist movements that devastated world democracy and reached the Brazilian executive power through the election of President Jair Messias Bolsonaro. Afterwards, the question of Brazilian constitutionalism and the protection of institutionality as a paradigm for maintaining democracy was questioned, as well as the role of the Federal Supreme Court in the defense of the Federal Constitution. Furthermore, the ways of understanding law in the context of positivist and neopositivist theory were studied from the perspective of the Hermeneutic Critique of Law by Lênio Streck and natural law by authors such as Ron Fuller and John Mitchel Finnis. Also, the judgment of ADPF 572 was exhaustively analyzed, in which the Federal Supreme Court declared the constitutionality of the Ordinance that gave rise to Inquiry 4.781, as well as the doctrinal position on the subject. Given this context, the work sought to answer what are the conditions of possibility, from the constitutional hermeneutics, to allow as an "appropriate response" the official action of the Federal Supreme Court as an investigation, processing and punishment body, setting limits on freedom of expression for the defense of institutions. Methodologically, the work stems from bibliographic reference research, using works that deal with the proposed theme, exploring concepts by renowned authors, categorizing them in a scientific proposal in order to contribute to the problematization. However, the hermeneutic phenomenological methodology is also adopted as a methodology, seeking to capture from the “zeitgeist” the ontological essence of the “thing” from the cacophony in existing communication. Alongside the facts that transpired during the work, it was essential to analyze what was reported by the main press vehicles, to build the ground on which the conclusions were based. The critical focus, having as an analysis clipping of the “fake news” Inquiry, will reside in extracting, the hermeneutically and constitutionally (un)sustainable (in)congruences, so that, it will become possible to expose and criticize the performance of the STF, a phenomenon that is currently a democratic safeguard. The dialectic is also essential to confront today's facts, especially news published by the mainstream press, which still carries signs of independence, aiming to demonstrate the current democratic conception of institutions and, notably, of the Federal Supreme Court. The research, of the bibliographic type, will be based on a contextualized interpretation of current elements, so that the items aim to express the institutional democratic confrontation and the (im)possibility of institutional dialogues in the light of Inquiry 4781.
Keywords: Inquérito 4.781; Democracia; Estado democrático de direito; Inquiry 4781; Democracy; Democratic rule of law; ACCNPQ::Ciências Sociais Aplicadas::Direito